PENGGUNAAN RAK PENJEMURAN KERUPUK UBI UNTUK PENINGKATAN EKONOMI MASYARAKAT DESA TALANG LINDUNG - Afdhal Chatra Perdana; Yelnim Yelnim; Cyntia Carolina (Jurnal Abdimas Bina Bangsa, 2023)
In the cassava cracker production process in Talang Lindungi Village, three sweet potato cracker business partners were found facing Masalah. Where  there are limited drying facilities for potato crackers that are still made from plastic mats, so the drying process takes a relatively long time. This is a service that aimsto improve the welfare of the three potato cracker business partners. The method of service activity consists of 3 stages: The initial stage, namely the analysis of the situation and condition of partners in the form of identification of problems and needs. The second stage is to provide drying rack equipment and training to potato cracker business partners. The third stage is monitoring and evaluation. The results of this community service show an increase in production volume and consistency of product quality, which can increase the household income of the three business partners